2022
DOI: 10.3390/ijerph192416827
|View full text |Cite
|
Sign up to set email alerts
|

Hyperglycemia in Pregnancy and Women’s Health in the 21st Century

Abstract: Hyperglycemia is the commonest medical condition affecting pregnancy and its incidence is increasing globally in parallel with the twin epidemics of diabetes and obesity. Both pre-pregnancy diabetes and gestational diabetes are associated with short term pregnancy complications, with the risk of immediate complications generally broadly rising with more severe hyperglycemia. In this article we firstly consider these risks and their optimal management during pregnancy and then broaden our scope to consider the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 128 publications
0
5
0
Order By: Relevance
“…Besides, higher OGTT 0 hour and OGTT 2 hours were found to be significant predictors of SGA when the glucose values were analysed as continuous variables. This may contribute to within the mild elevation range of blood glucose levels; blood glucose passes through the placental circulation to the fetus and extra glucose in the fetus is stored as body fat 43. There may be a protective mechanism ensuring that the fetus receives adequate nutrients within the normal range.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, higher OGTT 0 hour and OGTT 2 hours were found to be significant predictors of SGA when the glucose values were analysed as continuous variables. This may contribute to within the mild elevation range of blood glucose levels; blood glucose passes through the placental circulation to the fetus and extra glucose in the fetus is stored as body fat 43. There may be a protective mechanism ensuring that the fetus receives adequate nutrients within the normal range.…”
Section: Discussionmentioning
confidence: 99%
“…This may contribute to within the mild elevation range of blood glucose levels; blood glucose passes through the placental circulation to the fetus and extra glucose in the fetus is stored as body fat. 43 There may be a protective mechanism ensuring that the fetus receives adequate nutrients within the normal range. However, this does not imply that higher blood glucose levels are better.…”
Section: Discussionmentioning
confidence: 99%
“…This necessitates intensive medical therapy and often requires adjusted insulin administration to prevent threatening hyperglycemia for the fetus. In reaction to the stress of coexisting illnesses or drugs taken for the treatment of obstetrical issues, the elevated insulin resistance may also cause ketoacidosis [70].…”
Section: Evaluation During Preconceptionmentioning
confidence: 99%
“…2 HIP is associated with a significantly increased risk of adverse perinatal outcomes, including preeclampsia, birth injuries, increased caesarean section rates, and an increased incidence of type 2 diabetes mellitus in offspring. [3][4][5] The International Society for the Study of Hypertension in Pregnancy (ISSHP) defines PE as new onset hypertension and proteinuria after 20 weeks of gestation or with other end-organ damage, that affects 2-8% of pregnancies worldwide, and can lead to preterm delivery, fetal growth restriction, maternal convulsions, damage to vital organs such as the heart, liver and kidneys and in severe cases, maternal and fetal death. [6][7][8] It has been shown that HIP is associated with an increased risk of PE.…”
Section: Introductionmentioning
confidence: 99%